Tlingit interior displaying blankets, carvings, and flag-covered coffin, Wrangell, Alaska, 1887 - Partridge, William H.
Interior of large single room, wooden step down onto main floor. On main floor by stove is a coffin covered in an American flag, set on a table covered in a button blanket. A woman sits on the floor near it and other carvings. On the upper level, a man and woman sit on opposite sitrs of the coffin, surrounded by Tlingit carvings, wall hangings and clothing. Caption on mount: Alaska, U.S. Ft. Wrangel. Partridge Publisher. 69 Morrison St., Portland, Or. PH Coll 322.11